Bacteria simbion landscape (Oryctes rhinoceros L.) as a bioactivator for oil palm empty fruit bottle for organic mulsa - Marheni; Lubis, Lahmuddin (Talenta Publisher, 2019)
Oryctes rhinoceros is an important pest in oil palm plants attacking plants and immature plants. Utilization of oil palm empty fruit bunches in the field causes the spread and increase of O. rhinoceros attacks. The phenol compound and phenyl phenol released by decomposed oil palm empty fruit bunch attract O. rhinoceros to the organic material. The process of decomposition of oil palm empty fruit bunches 6-9 months resulted in an increase in pest population. O. rhinoceros larvae have symbiotic bacteria in their intestines and produce hydrolytic enzymes that have the potential and can be developed to degrade oil palm empty fruit bunch waste that is used as a composting starter. composting. The materials used in this study were larvae of O. rhinoceros instar 3, culture media of NA, NB, fungi, trichoderma, yeast and other materials that support the research. Tools used in scalpels, measuring cups, microscopes and others. The study was conducted at the Plant Disease Laboratory and Greenhouse, Agrotechnology Study Program, Faculty of Agriculture, University of North Sumatra, Medan from June 2019 to October 2019. This research used a Non Factorial Complete Randomized Design with 9 treatments and 3 replications. The results of the study were obtained 2 bacterial species namely Achromobacter SP and Bacillus SP then made as a composting activator. The use of this symbiont bacteria influences the physical and chemical factors of compost produced. As for physically obtained compost color in the treatment of P8 7.5 YR 2/1 (Black) while P0 7.5 YR 3/2 (Dark Brown). Compost has a soil aroma and temperature. Material reduction during composting from all treatments averaged 42.14%. The best C / N ratio is in the treatment of P7 (Bacillus + molasses) that is equal to 14.78% and the composting process lasts for 10 weeks.